Directory of Soviet officials (U.S. Government Printing Office)
United States of America. Department of State. Bureau of intelligence and research. Biographic directory ; 272. 1.Personnel in the Communist Party, government, and mass organizations of the U.S.S.R. and R.S.F.S.R. 1960. XX, 227 p. - With index